Effect of tumour necrosis factor-α inhibitor on serum level of dickkopf-1 protein and bone morphogenetic protein-7 in ankylosing spondylitis patients with high disease activity. (January 2014) - Korkosz, M; Gąsowski, J; Leszczyński, P; Pawlak-Buś, K; Jeka, S; Siedlar, M; Grodzicki, T
<x xml:space="preserve">Abstract</x> Objectives: To examine changes in serum levels of the bone remodelling molecules dickkopf-1 (Dkk-1), sclerostin, wingless-type protein-3a (Wnt-3a), and bone morphogenetic protein-7 (BMP-7) during 6 months of anti-tumour necrosis factor (anti-TNF) treatment in ankylosing spondylitis (AS) patients with high disease activity. Method: We included 40 patients with axial AS: 20 patients with high disease activity were assigned to treatment with TNF inhibitor and 20 with low disease activity were assigned to non-steroidal anti-inflammatory drug (NSAID) treatment. Markers of bone remodelling and inflammation were assessed at baseline and after 6 months. Results: In the TNF inhibitor-treated group Dkk-1 decreased significantly from 196.8 pg/mL [95% confidence interval (CI) 94.1–399.0] to 116.3 pg/mL (95% CI 38.0–301.6) and BMP-7 increased significantly from 1.4 pg/mL (95% CI 0–23.0) to 20.3 pg/mL (95% CI 4.9–41.3). There was a significant negative correlation between Dkk-1 and BMP-7 at 6 months (r = –0.64, p = 0.004) in this group. Non-parametric regression analysis adjusted for disease duration, age, sex, baseline modified Stoke's Ankylosing Spondylitis Spine Score (mSASSS), and baseline C-reactive protein (CRP) confirmed a statistically significant effect of treatment on time-related changes of Dkk-1 and BMP-7. Erythrocyte sedimentation rate (ESR), CRP, and also the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score decreased significantly in the anti-TNF-treated group. Conclusions: Among the potential biomarkers of bone remodelling in AS, Dkk-1 and BMP-7 displayed significant time alterations and correlative interactions during anti-TNF treatment.